Small town, great expectations: urbanization and beautification in Leh - Müller-Blondeau, Judith Christine; Dame, Juliane (South Asia multidisciplinary academic journal, 2016)
Urban modifications have considerably altered the appearance of Leh, a district capital in the Indian Transhimalaya, over the last few years. The beautification project in Leh is concentrated at and around the main bazaar and currently is the most visible and powerful instrument shaping the urban space. It is a subproject under the national “Urban Infrastructure Development Scheme for Small & Medium Towns” (UIDSSMT, Ministry of Urban Development 2009) and started in December 2013. Constructio...
Gesehen am 20.03.2017